Hemolysis and IgA‐antibodies against tissue transglutaminase: When are antibody test results no longer reliable?. Issue 4 (23rd November 2017) - Wolf, Johannes; Haendel, Norman; Remmler, Johannes; Kutzner, Carl Elias; Kaiser, Thorsten; Mothes, Thomas
Abstract : Background: Antibodies against tissue transglutaminase (TTG) of isotype IgA (IgA‐aTTG) represent reliable diagnostic markers to confirm or exclude celiac disease (CD). Hemolysis (HL) is an important pre‐analytical factor. HL can be quantified as HL index (HI) correlating with the concentration of free hemoglobin. TTG is abundant in erythrocytes and released upon HL. In immunoassays, the released TTG may interfere with binding of IgA‐aTTG to the coated TTG. Methods: We selected 17 HL‐free sera from children with biopsy‐confirmed CD: 7 with low‐positive (1‐5 multiples of upper limit of normal [×ULN]), 5 with intermediate (5‐10 × ULN) and 5 with high IgA‐aTTG (10‐15 × ULN). Sera were spiked with hemolysates resulting in HIs ranging from 12.5 to 800 (12.5‐800 mg/dL free hemoglobin). Results: IgA‐aTTG values were significantly decreased (>10%) after addition of hemolysates even if HL was invisible (HI <50). This effect is diagnosis‐relevant if IgA‐aTTG values are measured just below the cut‐offs: (i) 0.4‐1 × ULN at HI ≥25 (CD not excludable) and (ii) 8.5‐10 × ULN at HI ≥200 (diagnosis of CD without biopsy not possible). Antibodies against deamidated gliadin were not influenced by HL. Conclusions: IgA‐aTTG results in sera with HI ≥25 can yield inconclusive results. Therefore, those antibody results should be assessed only under consideration of the HI.